THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE LABOR MARKET AND EMPLOYMENT (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines the issues of the labor market and employment from the perspective of the impact of artificial intelligence. The main focus is on the impact of artificial intelligence on important elements of the labor market, namely employment opportunities, wages, and labor productivity. The author examines three aspects of the impact of artificial intelligence and automation on the labor market. First, the job replacement effect of artificial intelligence is studied, that is, changes that involve the use of machines to replace human labor in the labor process. It also examines methodologically how artificial intelligence and automation can affect labor productivity (productivity increase effect) and the demand for labor (regeneration effect).
Keywords: artificial intelligence, labor market, labor productivity effect, job replacement effect, regeneration effect that creates new jobs.